Pengaruh Steam dan Variasi Lapisan Terhadap Sifat Fisis dan Mekanis Papan Partikel Hibrida Kayu Jabon dan Bambu Betung: Effect of Steam and Layer Variation on The Physical and Mechanical Properties of Jabon Wood and Betung Bamboo Hybrid Particleboard - Muhamad, Soleh; Wijayanto, Arip; Nurhanifah, Nurhanifah; Mulyosari, Desy; Anggiriani, Siska (Fakultas Kehutanan Universitas Jambi, 2025)
ABSTRACT This study aims to assess the physical and mechanical properties of hybrid particleboard fabricated from jabon wood (Anthocephalus cadamba) and betung bamboo (Dendrocalamus asper) with the application of steam treatment and variations in the arrangement of particleboard layers. The steam conditioning was executed via autoclaving at a temperature of 126 ºC for a duration of 60 minutes under a pressure of 0.14 MPa to improve particle quality prior to the board manufacturing process. The particleboards were architected following a face/core/back schema with three layered variations, namely jabon particleboard, hybrid jabon/bamboo/jabon, and bamboo/jabon/bamboo. The adhesive agent utilized was urea-formaldehyde (UF), applied at a proportion of 10% relative to the oven-dry weight of the particles. The dimensional specifications of the particleboards were fixed at 30 × 30 × 0.9 cm³, targeting a density of 0.6 g/cm³. The appraisal of the physical and mechanical properties was conducted in strict adherence to JIS A 5908-2003, encompassing density, moisture content, water absorption, thickness swelling, modulus of rupture and modulus of elasticity. The empirical outcomes intimate that the hybrid particleboard with a bamboo/jabon/bamboo subjected to steam treatment manifested superlative performance, substantially augmenting the physical and mechanical properties made from jabon wood and betung bamboo. Keywords: betung bamboo, hybrid, jabon wood, particleboard, steam. ABSTRAK Penelitian ini memiliki tujuan untuk mengkaji sifat fisis dan mekanis papan partikel hibrida yang terbuat dari kayu jabon (Anthocephalus cadamba) dan bambu betung (Dendrocalamus asper) dengan penerapan perlakuan steam serta variasi susunan lapisan papan partikel. Perlakuan steam dilakukan menggunakan autoklaf dengan suhu 126 ºC dengan lama 60 menit dengan tekanan 0,14 MPa untuk meningkatkan kualitas partikel sebelum proses pembuatan papan. Papan partikel disusun dengan pola face/core/back dalam tiga variasi lapisan, yaitu papan partikel jabon, hibrida jabon/bambu/jabon, dan hibrida bambu/jabon/bambu. Perekat yang digunakan yaitu urea formaldehida (UF) sebanyak 10% dari berat kering partikel. Dimensi papan partikel adalah 30x30x0,9 cm³ dengan target kerapatan 0,6 g/cm³. Evaluasi sifat fisis dan mekanis mengikuti kriteria JIS A 5908-2003, mencakup kerapatan, kadar air, daya serap air, pengembangan tebal, modulus of rupture dan modulus of elasticity. Hasil penelitian mengindikasi bahwasanya papan partikel hibrida dengan susunan bambu/jabon/bambu dan perlakuan steam menghasilkan performa terbaik, serta mampu meningkatkan sifat fisis dan mekanis papan partikel berbahan kayu jabon dan bambu betung. Kata kunci: bambu betung, hibrida, kayu jabon, papan partikel, steam.